The Ecological Crisis and Environmental Ethics in the Novel Api Awan Asap by Korrie Layun Rampan - Umi Roisatul Mukaromah; Fatma Fadila; Lilis Setia Wardani; Asti Tiana Ningrum; Ayu Wandini; Purnomo Aji; Onok Yayang Pamungkas (Athena: Journal of Social, Culture and Society, 2026)
This research aims to analyze the representation of ecological crises, human relations with nature, as well as environmental ethics and human responsibility towards nature in the novel Api Awan Asap by Korrie Layun Rampan. This research uses a qualitative paradigm with a descriptive-interpretive approach through the hermeneutic method to interpret the deepest meaning behind the literary text. The source of data for this research is the novel Api Awan Asap by Korrie Layun Rampan published by Gramedia Widiasarana Indonesia in 2015. The research data is in the form of words, sentences, and discourses contained in the novel Api Awan Asap which represents the ecological crisis and human responsibility towards nature. The results of the study show that this novel represents an ecological crisis through the depiction of exploitative activities such as deforestation, land burning, and appropriation of customary territories that result in air pollution, land degradation, and ecological disasters. The relationship between humans and nature is depicted through the practice of local wisdom of indigenous peoples who live in harmony with the environment and use nature wisely. The moral principles of the environment and human obligations to nature are manifested through a value system that respects nature, tradition-based forest management, and educational and humanitarian approaches in an effort to prevent environmental damage. From the findings, it can be concluded that literary works function as instruments in building ecological awareness and motivating responsible human actions towards nature conservation.